'A tale in three cities: Tracing identity in the realisation of an independent Poland.' Biography and Exegesis. - Singleton, Helen Caroline Mackay (Curtin University, 2023)
Secrets shroud a Polish Australian’s life in three historical and geopolitical settings: Lwow, Galicia Imperial Austria and Poland (1904-1939); wartime Edinburgh, Scotland (1940-1951); and Cold War Australia (1951-1991). The creative non-fiction, two-generation, auto/biography, and exegesis apply an interdisciplinary research approach to explore a life history’s values, agency, and multicultural origins, articulated to societal themes of war, exile, migration, leadership, diaspora, and resettlement in twentieth century’s international geopolitical context, with relevance to current events in Ukraine.